The Analysis of Among Relationship Between Hotel Image and Customer Loyalty Facets Terms of Hotel Services and Products (Case Study : Sapadia Hotel Simalungun District) - Tina Taviani (Politeknik Pariwisata Medan, 2021)
The relationship that exists between the seller (hotel party) and the buyer (hotel guest) in the future depends on the level of loyalty of the customers themselves, this study describes the extent to which the image of the hotel provides services to customers, where the service and image of a hotel are both can lead to a sense of loyalty from customers of a hotel. Where it can be drawn from the final results of this study that the image of the hotel and service is closely related in order to produce customer satisfaction, it can be seen in the variable constant value of 2.681, meaning that if the value of the independent variable (X1 and X2) is 0, then service is 2.681. The hotel image regression coefficient value is 0.271 from the hotel image variable (X1) with the assumption that the customer loyalty variable (X2) is constant (a) is 0 (zero), then the service increases by 0.271. And simultaneously the hotel image variable (X1) and customer loyalty (X2) simultaneously have a significant effect on services at Sapadia Hotel Siantar, Simalungun Regency. This can be seen from the value of Ftable = f (k; n - k), F- (2; 45-2), Ftable = (2; 43) = 3.21 that the Fcount value is 85,864> from the Ftable value is 3.21 and a significant value is 0.000. <from alpha value 0.05. Then the decision taken H0 is rejected. H3 is accepted. The acceptance of H3 shows that the independent variable consisting of hotel image (X1) and customer loyalty (X2) is able to explain the diversity of the dependent variable (Y). Thus the variables of hotel image and customer loyalty simultaneously have a positive and significant effect on services at Sapadia Hotel Siantar, Simalungun Regency.